2021
DOI: 10.7759/cureus.17088
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Strokes With Alteplase (Tissue Plasminogen Activator)

Abstract: In the pediatric population, ischemic stroke is rare. Pediatric patients with acute ischemic stroke are eligible for intravenous thrombolysis and/or mechanical thrombectomy. However, due to the rare occurrence of strokes and national shortage of pediatric neurologists, timely diagnosis and appropriate treatment can be challenging. We report a case of a 16-year-old female who presented with an acute ischemic stroke to our adult comprehensive stroke program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In general, our review shows that the time to onset of IVT is extended in some cases but is safe in pediatric stroke according to symptomatic hemorrhagic rates. Filatov et al 86 observed that alteplase administration in children is associated with risks similar to those observed in adults, and can restore cerebral blood and reduce brain damage in pediatric strokes.…”
Section: Discussionmentioning
confidence: 98%
“…In general, our review shows that the time to onset of IVT is extended in some cases but is safe in pediatric stroke according to symptomatic hemorrhagic rates. Filatov et al 86 observed that alteplase administration in children is associated with risks similar to those observed in adults, and can restore cerebral blood and reduce brain damage in pediatric strokes.…”
Section: Discussionmentioning
confidence: 98%
“…The primary treatment is based on the supportive therapy. Current recommendations are to apply thrombolytic agents or clot-dissolving drugs, such as alteplase (an intravenous recombinant tissue plasminogen activator-rTPA) in children with acute ischemic stroke recognized within the recommended 4.5 h therapeutic window [158,161,162]. As the administration of a thrombolytic therapy may increase the risk of intracranial hemorrhage in children, a pediatric hematologist, in addition to a neurologist, should be included in the assessment of therapeutic possibilities.…”
Section: Up-and-coming Therapeutic Modalities and Approachesmentioning
confidence: 99%